Within walls private life in the German Democratic Republic - Betts, Paul, 1963- (Oxford University Press, 2010)
A history of private life in the German Democratic Republic showing how the private sphere assumed central importance in the GDR from the very outset, and revealing the myriad ways in which privacy was expressed, staged and defended by citizens living in a communist society.